Public Relations Management in Enhancing Student Enrolment at Madrasah Aliyah Negeri Lombok Barat - Musta'in; Fatimatuzzohroq; Muhamad Fahmi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2026)
This study aims to analyse public relations management in increasing student enrolment at Madrasah Aliyah Negeri Lombok Barat. The research employed a qualitative approach with a descriptive research design. The research subjects were selected through purposive sampling and included the head of the madrasah, the vice principal for public relations, one student, and one student’s parent. Data were collected through non-participant observation, semi-structured interviews, and documentation studies. The collected data were analysed using an interactive analysis model comprising data reduction, data display, and conclusion drawing and verification. Data validity was ensured through technique triangulation. The findings indicate that public relations management at MAN Lombok Barat is implemented systematically through the core management functions of planning, organizing, implementation, and evaluation, particularly in the New Student Admission (PPDB) program. The public relations strategies applied include information dissemination through digital and print media, collaboration with internal and external stakeholders, and social activities aimed at strengthening the madrasah’s relationship with the community. The increase in student enrolment is influenced by community satisfaction with the quality of educational services, the positive image of the madrasah, and the active participation of the madrasah community and alumni. This study provides both theoretical and practical contributions to the development of Islamic Education Management, particularly in the management of public relations as a strategic approach to enhancing the sustainability of Islamic educational institutions.